Historical separation and present-day structure of common dolphinfish (Coryphaena hippurus) populations in the Atlantic Ocean and Mediterranean Sea. (6th December 2018) - Maggio, Teresa; Allegra, Alessandro; Andaloro, Franco; Pedro Barreiros, João; Battaglia, Pietro; Butler, Christopher M; Cuttitta, Angela; Fontes, Miguel Rodrigues Jorge; Freitas, Rui; Gatt, Mark; Karakulak, F Saadet; Macias, David; et al.
Abstract: The common dolphinfish ( Coryphaena hippurus ) is an epipelagic, mid-trophic level, highly migratory species distributed throughout the world's tropical and subtropical oceans in waters greater than 20°C. Life-history variables, migratory behaviour, and genetic markers have been used to define major stocks in the central Atlantic Ocean and Mediterranean Sea. Here, we used the mitochondrial DNA gene NADH subunit 1 (688 bp) to test for differences between population groups. A total of 103 haplotypes were detected among 203 fish. Gene diversities in samples were large and similar among populations (mean h = 0.932; range 0.894–0.987), but nucleotide diversities varied widely among samples (range π = 0.004–0.034) and appear to reflect population histories. Principal component analysis revealed two large populations groups, and the analysis of molecular variation and pairwise values of ΦST resolved population structure within these groups. Populations in the eastern Atlantic and Mediterranean showed the largest amounts of divergence from one another (ΦCT = 0.331). Adult movement and biophysical barriers to larval dispersal may explain contemporary differences between stocks, but the divergent populations in the Mediterranean Sea are likely due to isolations by cold temperature barriers during Pleistocene glaciations. The geographically large stock groupings require international cooperation in the harvest management and conservation of local dolphinfish populations.